# How do you solve #3/(x-3)=x/(x-3)-3/2#?

x=3

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation 3/(x-3) = x/(x-3) - 3/2, we can start by multiplying both sides of the equation by (x-3) to eliminate the denominators. This gives us 3 = x - 3(x-3)/2. Simplifying further, we have 3 = x - (3x - 9)/2. Multiplying both sides by 2 to clear the fraction, we get 6 = 2x - (3x - 9). Combining like terms, we have 6 = 2x - 3x + 9. Simplifying, we get 6 = -x + 9. Subtracting 9 from both sides, we have -3 = -x. Multiplying both sides by -1, we get 3 = x. Therefore, the solution to the equation is x = 3.

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7